Burn ebook - Heller, Peter (2024)
From the best-selling author of The Dog Stars and The Last Ranger, a novel about two men—friends since boyhood—who emerge from the woods of rural Maine to a dystopian country racked by bewildering violence Every year, Jess and Storey have made an annual pilgrimage to the most remote corners of the country, where they camp, hunt, and hike, leaving much from their long friendship unspoken. Although the state of Maine has convulsed all summer with secession mania—a mania that has simultaneously spread across other states—Jess and Storey figure it’s a fight reserved for legislators or, worst-case scenario, folks in the capital. But after weeks hunting off the grid, the men reach a small town and are shocked by what they find: a bridge blown apart, buildings burned to the ground, and bombed-out cars abandoned on the road. Trying to make sense of the sudden destruction all around them, they set their sights on finding their way home, dragging a wagon across bumpy dirt roads, scavenging from boats left in lakes, and dodging armed men—secessionists or U.S. military, they cannot tell—as they seek a path to safety. Then, a startling discovery drastically alters their path and the stakes of their escape. Drenched in the beauty of the natural world and attuned to the specific cadences of male friendship, even here at the edge of doom, Burn is both a blistering warning about a divided country’s political strife and an ode to the salvation found in our chosen families.